Reading habits of teachers in four government-aided secondary schools (mission schools) in Kuching district - Daik, Sanjan (2006)
Specifically, this study attempts to investigate the different types of reading materials, frequency of reading, teaching load and factors that influence reading habits among teachers in the four (4) government-aided secondary schools (Mission Secondary Schools) in Kuching District. The respondents in this study were 118 teachers from the four schools. The main methodology employed in this study was a survey questionnaire. Interviews were also conducted on twenty (20) of the teachers who had responded to the questionnaires. The data were analysed and concluded that most of the teachers have poor reading habits. The findings showed that most of the teachers read both academic and non-academic reading materials, having reading frequency of only a few hours a week and prefer to read at home while some teachers have heavy teaching load that inhibit their reading habits. Based on this study, it will raise awareness on the importance of readings among teachers. The result of this study has an implication on the importance of inculcating the reading habit among school children at an early age.